Tribocorrosion Behavior of Calcium- and Phosphorous-Enriched Titanium Oxide Films and Study of Osteoblast Interactions for Dental Implants - Alves, S. A.; Bayón, R.; de Viteri, V. Saénz; Garcia, M. P.; Igartua, A.; Fernandes, M. H.; Rocha, L. A. [UNESP] (Springer Nature, 2015)
Titanium (Ti) dental implants are frequently exposed simultaneously to a corrosive environment and cyclic micromovements at implant/abutment and implant/bone interfaces, becoming part of a tribocorrosion system. Thus, wear debris and corrosion products/ions can be released to peri-implant tissues and induce inflammatory reactions leading to implant failure. Moreover, the poor osseointegration is also one of the main problems affecting dental implants lifetime. Surface modification strategies have been proposed to design novel Ti oxide-based multifunctional surfaces that are able to simultaneously improve cellular functions and provide enhanced tribocorrosion resistance. Hence, the main objective of this work was the synthesis of Calcium (Ca)- and Phosphorous (P)-enriched Ti oxide films aimed to display superior wear/corrosion performance and simultaneously, to enhance osteoblast–material interactions. Ca- and P-enriched films were synthesized by plasma electrolytic oxidation (PEO) and their characteristics were assessed by Field emission scanning electron microscopy, profilometry, energy-dispersive X-ray spectroscopy, X-ray diffraction, and water contact angle measurements. PEO-treated samples were subjected to pin-on-disk reciprocating sliding tests in artificial saliva at 37 °C. The viability of MG63 cells cultured on PEO-treated samples was investigated by MTT assay, and their adhesion ability by SEM and confocal laser scanning microscopy. The wear/corrosion behavior of Ti was improved after PEO treatments and the electrolyte composition appeared to play a crucial role both on its corrosion tendency and mechanical wear resistance. It is believed that this improvement is related to the higher rutile/anatase ratio exhibited by Ca- and P-enriched surfaces. Osteoblasts were well spread on these surfaces displaying improved viability/proliferation compared to Ti.
Keywords: Dental Implants; Osteoblasts; Oxide films; Plasma electrolytic oxidation; Titanium; Tribocorrosion